Application of essential oils as a natural and alternate method for inhibiting and inducing the sprouting of potato tubers. (30th June 2019) - Shukla, Samvedna; Pandey, Shiv Shanker; Chandra, Muktesh; Pandey, Alok; Bharti, Nidhi; Barnawal, Deepti; Chanotiya, Chandan Singh; Tandon, Sudeep; Darokar, Mahendra Pandurang; Kalra, Alok
Highlights: Treatment of palmarosa and ajwain oils inhibited sprouting of potato tubers. Treatments of lemon grass and clove oils induced sprouting of potato tubers. Selected oils treatments modulated accumulation of reducing sugars and ethylene. Selected oils treatments modulated expression of key genes of tuber-sprouting. Selected oils can be used for reducing post-harvest losses of potato crop. Abstract: Use of harmful chemicals and expensive maintenance of cold-storage conditions for controlling sprouting are among the major problems in potato storage. Here, 20 essential oils (EOs) were tested for their sprouting-inhibiting and sprouting-inducing activities. Overall, treatments of lemon grass (LG) and clove (CL) oils could induce sprouting whereas palmarosa (PR) and ajwain (AZ) oils could inhibit sprouting of potato tubers at normal-room-temperature (25 ± 2 °C) storage. Selected-EOs treatments affected sprouting by modulation of accumulation of reducing sugars, ethylene, and expression of genes involved in tuber-sprouting such as ARF, ARP, AIP and ERF . Surprisingly, 7-days AZ-treatments could inhibit sprouting for 30-days which was mediated via damaging apical meristem. However, LG- and CL-treated tubers could produce enhanced potato yield as well. Present work clearly demonstrates that selected-EOs can be used as a promising eco-friendly approach for inducing/inhibiting sprouting of potato tubers during potato storage and those enhancing sprouting can be used for enhancing productivity.